Empowerment of diversity in the Nepalese corporate sector (Quest Journal of Management and Social Sciences, 2019)
Background: There are numerous policy developments undergoing addressing the issue of gender empowerment and social inclusion (GESI) in the corporate sector with an aim to socio-economic mainstreaming of the backward groups but the government programs and the national youth policy may still be lacking the effective implementation for addressing the needs, rights and aspirations of the overall backward people. The present researchers perceived strong need for closer assessment of effectiveness of the policy framework to promote diversity, especially in the corporate sector.For this, the paper, as a whole, discusses within the broader framework of equality and inclusivity, the theme of women in corporate governance with particular reference to Nepalese corporate sector.Objectives: This study was aimed to explore the present scenario of empowerment of diversity in the Nepalese corporate sector.Methods: Fully based on desk research crafted on qualitative paradigms of study. Secondary data were used to collect the information on the issues, trends, matters relating to Gender equality and social inclusion (GESI) and youth empowerment.Results: Effective compliance of corporate governance (CG) has played the significant role in promoting GESI and youth empowerment in the Nepalese corporate sector under changing context of the country and beyond.Conclusions:As a result of multi-dimensional transformation of national structural system, there has been increasing sensitivity and application of GESI sensitive planning and implementation in the Nepalese corporate sector. Such a practice would serve instrumental in empowering women, youth and other marginalized sections of the society.Implications: GESI compliance and youth empowerment in corporate and other service sectors should be made a part of national strategic direction at all levels of institutional governance and disciplining.